Analisis SWOT Sebagai Strategi Peningkatan Daya Saing Bakso Rosso Di Hartono Mall Yogyakarta SWOT Analysis As A Strategy To Increase The Competitiveness Of Bakso Rosso At Hartono Mall Yogyakarta - Ita Oktarita (EBBANK, 2022)
This research is expected to produce new strategies that are useful not only for writers and academics as literacy material, but also for strategy makers in creating new strategies and Bakso Rosso can continue to maintain a positive, innovative image and implement new strategies in their business. This research is included in the type of qualitative descriptive research, because it aims to describe the state of the phenomenon in the field. From the TOWS matrix, the largest number is shown in the ST (Strenght – Threat) strategy of 5.49 where Bakso Rosso performs a defensive strategy by applying strategies to deal with threats. Product diversification that is more optimized, in addition to selling ready-to-eat products, is not wrong if it focuses on the target market, namely hotels and restaurants that use meatballs as one of the food servings by becoming one of their suppliers